2021
DOI: 10.1155/2021/1858974
|View full text |Cite|
|
Sign up to set email alerts
|

Changes and Prognostic Value of lncRNA CASC9 in Patients with Advanced Colon Cancer after Chemotherapy

Abstract: Objective. Colon cancer (CC) shows a gradual increasing incidence in recent years, and chemotherapy is a frequently adopted treatment for patients with middle or advanced colon cancer (ACC), but it lacks prognostic markers after CC. Methods. The changes of lncRNA CASC9 in 58 patients with CC were determined using a real-time quantitative PCR (qRT-PCR) assay before and after chemotherapy, and the correlation of serum lncRNA CASC9 with efficacy of FOLFOX4 regimen (oxaliplatin + calcium folinate + fluorouracil) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Abnormal expression of various lncRNAs in human cancers is an essential cause of chemoresistance [ 28 30 ]. For example, Xu et al [ 29 ] found patients with colon cancer with increased expression of lncRNA CASC9 suffered an unfavorable chemotherapy effect [ 31 ]. Here, we found LINC01871 was dramatically downregulated in clinical CRC samples, and patients with low-expressed LINC01871 had worse survival.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of various lncRNAs in human cancers is an essential cause of chemoresistance [ 28 30 ]. For example, Xu et al [ 29 ] found patients with colon cancer with increased expression of lncRNA CASC9 suffered an unfavorable chemotherapy effect [ 31 ]. Here, we found LINC01871 was dramatically downregulated in clinical CRC samples, and patients with low-expressed LINC01871 had worse survival.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%